The role of place attachment in offline and online retail stores - Jokinen, Olga (2019)
As the online environment in the retail context has substantially grown managers are keen on finding new ways to commit customers to their stores. Place attachment has begun to emerge in the marketing literature as a possibility to hold on to and cherish customers. The role of place attachment in commercial settings is still a bit vague. Researchers and managers have yet to discover the effects that place attachment could have on consumers' behavioral outcomes.